2022
DOI: 10.1080/14782804.2022.2061433
|View full text |Cite
|
Sign up to set email alerts
|

Experience of economic hardship and right-wing political orientation hinder climate concern among European young people

Abstract: Experience of economic hardship and right-wing political orientation hinder climate concern among European young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The received wisdom has been that the salience of the climate issue for individuals is related to a number of aggregate-level 'objective variables' (Lewis et al, 2019), such as economic affluence (Kim and Wolinsky-Nahmias, 2014), a country's level of vulnerability to climate change, levels of income (Dunlap and York, 2008), unemployment, and the perception that one's economic situation has worsened. In contrast with those expectations, studies have found mixed results and been largely unsupportive of the income-climate concern argument (Lewis et al, 2019;Uba et al, 2021).…”
Section: Social Class and Climate Changementioning
confidence: 88%
See 1 more Smart Citation
“…The received wisdom has been that the salience of the climate issue for individuals is related to a number of aggregate-level 'objective variables' (Lewis et al, 2019), such as economic affluence (Kim and Wolinsky-Nahmias, 2014), a country's level of vulnerability to climate change, levels of income (Dunlap and York, 2008), unemployment, and the perception that one's economic situation has worsened. In contrast with those expectations, studies have found mixed results and been largely unsupportive of the income-climate concern argument (Lewis et al, 2019;Uba et al, 2021).…”
Section: Social Class and Climate Changementioning
confidence: 88%
“…The control variables in our analysis also yielded some interesting results. We know from existing research that generational variables are important determinants of attitudes toward environment and climate change, with concern regarding those issues particularly strong among young people (Uba et al, 2021). In our study, age was strongly and negatively correlated with confidence in any of the four strategies: that is, younger cohorts reported less confidence than older protesters in all of science, governments, companies and the market, and lifestyle choices to tackle environmental issues (Figure 5), although that effect was not robust in some model specifications.…”
Section: Social Class and Strategies To Address The Climate Crisismentioning
confidence: 99%